2016
DOI: 10.1007/s11229-016-1198-6
|View full text |Cite
|
Sign up to set email alerts
|

The ‘Alice in Wonderland’ mechanics of the rejection of (climate) science: simulating coherence by conspiracism

Abstract: Science strives for coherence. For example, the findings from climate science form a highly coherent body of knowledge that is supported by many independent lines of evidence: greenhouse gas (GHG) emissions from human economic activities are causing the global climate to warm and unless GHG emissions are drastically reduced in the near future, the risks from climate change will continue to grow and major adverse consequences will become unavoidable. People who oppose this scientific body of knowledge because t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 95 publications
3
53
0
3
Order By: Relevance
“…For example, belief polarization Jern, Chang, & Kemp, 2009) can be accommodated within a rational Bayesian framework, and it has been shown that Bayesian agents can form persistent "echo chambers," enclosed epistemic bubbles in which agents share most beliefs (Madsen, Bailey, & Pilditch, 2018). The use of rational agents also seemed advisable in light of several suggestions that climate denial can be considered a rational enterprise Lewandowsky, Cook, & Lloyd, 2016), notwithstanding its wholesale dismissal of scientific evidence.…”
Section: Influence and Seepagementioning
confidence: 99%
See 1 more Smart Citation
“…For example, belief polarization Jern, Chang, & Kemp, 2009) can be accommodated within a rational Bayesian framework, and it has been shown that Bayesian agents can form persistent "echo chambers," enclosed epistemic bubbles in which agents share most beliefs (Madsen, Bailey, & Pilditch, 2018). The use of rational agents also seemed advisable in light of several suggestions that climate denial can be considered a rational enterprise Lewandowsky, Cook, & Lloyd, 2016), notwithstanding its wholesale dismissal of scientific evidence.…”
Section: Influence and Seepagementioning
confidence: 99%
“…Although we modeled denial by including a bias parameter, it does not follow that resistance to evidence is "irrational." On the contrary, denial has been identified as a rational political operation of considerable effectiveness (Lewandowsky, Cook, & Lloyd, 2016), and even under a fully Bayesian approach, resistance to evidence can be modeled by inclusion of auxiliary hypotheses Gershman, 2018).…”
Section: Implications and Potential Interventionsmentioning
confidence: 99%
“…There are a variety of arguments and rhetorical strategies employed in climate misinformation, some of which are mutually contradictory (Lewandowsky, Cook, and Lloyd, 2016). Identifying and analyzing these arguments yields insights into the psychology driving climate science denial, and provides foundational frameworks that inform refutational strategies.…”
Section: Arguments and Techniques In Climate Misinformationmentioning
confidence: 99%
“…Esta línea argumental ya la expresaron Kahan et al (2011) al señalar cifras de consenso (entre el 45% y 15%) sobre la responsabilidad humana en el aumento de las temperaturas que relacionaron con atribuciones ideológicas y culturales. En la misma línea se encuentran también los textos de Bedford (2010), Bedford y Cook (2013), Benestad et al (2013), Kahan (2015) y Lewandowsky et al (2013Lewandowsky et al ( , 2016, muestras del evidente grado de ideologización que el debate ha alcanzado. Liu et al (2015) analizaron 1350 testimonios de 253 audiencias en el Congreso de EEUU (periodo 1969-2007) de los que 752 (55,7%) fueron de científicos, y catalogaron su opinión sobre si existe un cambio del clima y qué efecto tiene el hombre, pero sin señalar causa concreta.…”
Section: Otros Textosunclassified
“…Los defensores del planteamiento del IPCC, que en sus versiones más radicales reducen la hipótesis a que el hombre es el causante del cambio del clima por la emisión de CO 2 , llegan a lo absoluto al afirmar que se ha alcanzado la denominada "settled science", la ciencia definitiva, y que el debate está cerrado. En su argumentación afirman que (i) una cosa es disentir y otra crear infundios, (ii) que la discrepancia puede ser legítima e ilegítima, porque la discrepancia puede esconder oscuras intenciones ligadas a una conspiración para desinformar a la sociedad (Biddle y Leuschner, 2015), y por último (iii) se defiende la tesis argumentando que está basada en el consenso científico (Benestad et al, 2013;Bedford y Cook, 2013;Lewandowsky et al, 2013Lewandowsky et al, , 2016. O dicho de otro modo: están en posesión de la absoluta verdad.…”
Section: El Consenso El Disenso Y El Debateunclassified